Experimental Study of Polymer Concrete Material with SBR Latex for Bridge Pier: Compressive Test, Tensile Test, and Workability on Cylinder and Steel Samples - Justitiannisa, Innino; Gunadi, Riawan (Jurnal Teknik Sipil, 2025)
Concrete is a fundamental material in civil engineering structures due to its high compressive strength and durability. However, its low tensile strength, high permeability, and tendency to crack under environmental and mechanical stress limit its long-term performance, especially in substructures such as bridge piers exposed to dynamic and aggressive conditions. This study investigates the effect of incorporating 10% Styrene-Butadiene Rubber (SBR) Latex by weight into a polymer-modified concrete mix. The objective is to evaluate its mechanical behavior and workability as a preliminary step toward application in full-scale bridge pier construction. The concrete was designed using the Ohama method, which considers the interaction between polymer content and water"“cement ratio, while a dry-mix method was adopted to ensure uniformity and ease of implementation in field applications. Laboratory testing was conducted to evaluate the compressive strength at curing ages of 3, 7, and 28 days using cylindrical specimens (150 mm Ã— 300 mm). The tensile strength of reinforcing bars (Ã˜8 mm, Ã˜10 mm, and Ã˜16 mm) was evaluated using a Universal Testing Machine (UTM), while slump testing was conducted to determine workability. The results showed that the modified concrete reached a compressive strength of 29.86 MPa at 28 days, or 99.53% of the target strength (f"²c = 30 MPa). A slump value of 12 cm indicated improved cohesion and workability, while tensile tests confirmed the reinforcement"™s structural performance. A bridge pier prototype was also developed, with a column size of 0.25 Ã— 0.25 Ã— 1.68 m and a column head of 1.20 Ã— 0.55 Ã— 0.36 m. Overall, the incorporation of 10% SBR latex enhanced the mechanical and rheological properties of concrete, supporting its potential for use in durable bridge pier applications.